Performance Analysis of Certification Institutions of Marine and Fisheries Professions from 2019 to 2023 - Imron Natsir; Eny Triastuti (International Journal of Management Science and Information Technology, 2024)
This research aims to analyze the performance of the Professional Certification Institute (LSP KP) for Marine and Fisheries during the period of 2019-2023. The performance of the LSP KP is measured based on indicators such as the number of certifications issued, the pass rate of competency test participants, and the level of stakeholder satisfaction. Data was collected through surveys, interviews, and related document analysis. The analysis results indicate an improvement in performance regarding the number of certifications issued; however, there are still challenges in service quality and the efficiency of the certification processing time. This research also identifies the factors that influence the performance of LSP, such as the availability of resources, the competence of assessors, and regulatory policies. The main conclusion of this research is that although the performance of LSP KP has improved, further enhancements are needed to reach higher standards. Recommendations are made for strengthening the capacity of assessors, improving infrastructure, and refining operational procedures. The implications of these recommendations include an improvement in the quality of certification and industry trust in LSP KP, which can ultimately contribute to enhancing the competitiveness of the workforce in the maritime and fisheries sector.